The role of the plantation elite of PT PTPN IV Bandar Pasir Mandoge Unit in the 2024 presidential and vice presidential elections - Sitorus, Azri; Fauzan , Indra (Priviet Social Sciences Journal, 2025)
The Role of the Plantation Elite of PTPN IV Bandar Pasir Mandoge Unit in the 2024 Presidential and Vice Presidential Elections, particularly in influencing the political participation of employees in the plantation environment. Although management officially claims neutrality and supports honest and fair democracy, there are indications of systematic mobilisation and political direction by plantation elites, including by managers towards foremen and supervisors. This has led to unrest, demonstrations, and reports to the Election Supervisory Agency (Panwaslu) and the Election Supervisory Body (Bawaslu). This study uses Mosca`s elite theory and Soekanto's role theory to analyze elite power in the work structure and its impact on freedom of choice. The results show that despite claims of neutrality, in reality, the practice of elite power has the potential to influence election results in plantation areas. This study emphasizes the importance of election monitoring in closed work areas such as plantations to ensure democratic and pressure-free elections. Based on the methods and theories used, the results of this study show that power in society tends to be concentrated in small, organized groups that have access to strategic resources. In this context, plantation elites such as managers, foremen, and supervisors play an important role in directing the political choices of employees through various forms of mobilization, guidance, and even the installation of campaign materials in the plantation environment.